Genomic diversity in flavobacterial pathogens of aquatic origin. (May 2020) - Kumru, Salih; Tekedar, Hasan C.; Blom, Jochen; Lawrence, Mark L.; Karsi, Attila
Abstract: Flavobacterium species are considered important fish pathogens in wild and cultured fish throughout the world. They can cause acute, subacute, and chronic infections, which are mainly characterized by gill damage, skin lesions, and deep necrotic ulcerations. Primarily, three Flavobacterium species, F. branchiophilum, F. columnare, and F. psychrophilum, have been reported to cause substantial losses to freshwater fish. In this study, we evaluated genomes of 86 Flavobacterium species isolated from aquatic hosts (mainly fish) to identify their unique and shared genome features. Our results showed that F. columnare genomes cluster into four different genetic groups. In silico secretion system analysis identified that all genomes carry type I (T1SS) and type IX (T9SS) secretion systems, but the number of type I secretion system genes shows diversity between species. F. branchiophilum, F. araucananum, F. chilense, F. spartansii, and F. tructae genomes have full type VI secretion system (T6SS). F. columnare, F. hydatis, and F. plurextorum carry partial T6SS with some of the T6SS genes missing. F. columnare, F. araucananum, F. chilense, F. spartansii, F. araucananum, F. tructae, Flavobacterium sp., F. crassostreae, F. succinicans, F. hydatis, and F. plurextorum carry most of the type IV secretion system genes (T4SS). F. columnare genetic groups 1 and 2, Flavobacterium sp ., and F. crassostreae encode the least number of antibiotic resistance elements. F. hydatis, F. chilense, and F. plurextorum encode the greatest number of antibiotic resistance genes. Additionally, F. spartansii, F. araucananum, and chilense encode the greatest number of virulence genes while Flavobacterium sp. and F. crassostreae encode the least number of virulence genes. In conclusion, comparative genomics of Flavobacterium species of aquatic origin will help our understanding of Flavobacterium pathogenesis. Highlights: Genomes of 86 Flavobacterium species isolated from aquatic hosts were evaluated. Flavobacterium genomes contained 11 antibiotic resistance gene classes. Flavobacterium genomes contained 121 predicted virulence genes. All genomes carry type I and type IX secretion systems. Some Flavobacterium species have complete T6SS.